Environmental education in rural settlements: a Social Technology for environmental conservation and income generation - Gama, Andreza Angelica Frota; Mello, Andrea Hentz (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The present article deals about environmental education as a Social Technology, developed in rural settlements in order to benefit from the construction of new habits and alternatives involving the reduction of environmental degradation with income generation. Through a literature review of some successful experiences are pointed to assumptions that must be understood to undertake the change of consciousness and attitudes in families settled as: a qualitative approach; the shared vision; the problematization of questions for decision of the technology applied. Points out that the actions should be developed in the medium and long term, with a view to continuity and the permanence of the pursuit of knowledge, leading to a cultural vision of reality to ensure improved relations man, land and environment.